Analisis Potensi Bahaya Kecelakaan Menggunakan Metode Hirarc: (Studi Kasus : Jalan Purbalingga – Pemalang) - Berliana Gusna Mahedewanti; Revalina Anggraeni Winanda; Rika Ariani; Marcello Yoga Rivaldo Lazarus; Suprapto Hadi; Frans Tohom (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
The Purbalingga–Pemalang road has become a site of frequent traffic accidents due to its steep slopes, sharp curves, and lack of adequate road safety infrastructure. This study aims to assess the level of traffic accident risk using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method, with the goal of identifying high-risk segments and dominant contributing factors. Primary data were collected through field inspections and hazard identification surveys, while secondary data were obtained from police accident reports over the past three years. Analysis focused on road conditions, safety facilities, and environmental factors. Results indicate that Segment 4 is the most hazardous, accounting for nearly 47% of accidents involving minor injuries and one fatality. Key risk factors include damaged pavement, poor visibility due to overgrown vegetation, lack of guardrails, and malfunctioning traffic signals. The risk assessment classified several segments as having moderate to high risk levels. These findings underline the urgent need for road surface repairs, improved traffic signage, vegetation management to enhance visibility, and stricter law enforcement. The study highlights the importance of integrating hazard-based risk assessment methods in transport planning and infrastructure maintenance. By addressing these critical issues, it is expected that traffic accidents on this road can be significantly reduced, thus improving overall road safety for all users.